(untitled) (Global Journal of Computer Science and Technology, 2024)
In this study cyber security test platform aims to evaluate the vulnerabilities of cyber-attack exercises to review cyber security challenges In the introduction section brief overview of the research context has been provided by developing research questions and determining the problem statements In the Literature review section different articles will be analyzed for gathering better information about the research questions Secondary research methodology will be utilized in this research paper and brief explanation of chosen research methodology has been mentioned in the third section The main purpose of this research paper is to conduct a proper platform which can detect cyber-attack and decrease the attack numbers This paper will provide several improvement of the proposed platform for developing the scalability